Comparison between survival and severe models of malaria infection for better understanding of the underlying disease pathogenesis - Chong, Wing Chui (2013)
Different host-parasite combination will result in varied malaria presentation and outcome. In this preliminary study, ICR mice and Sprague dawley rats were inoculated intraperitoneally with 2 x 107 parasitized red blood cells (pRBCs) obtained from donor mouse pre-infected with P. berghei ANKA (PbA). Control to malaria-infected animals received an equivalent volume and dilution of normal RBC through the same route of administration. The susceptible mice which serve as severe model demonstrated a parasitaemia level of approximately 75% together with a progressive decrease in body weight and temperature before succumb to the infection. Malarial rats that survived the infection developed moderate level of parasitaemia (45%) and insignificant changes in terms of illness symptoms and behavioural responses followed with gradual resolution. Multiple organ dysfunctions is also an important contributor towards malaria-associated mortality, hence histopathological examination was performed on H&E stained tissue obtained from five vital organs including brain, liver, spleen, kidney and lung. Some of the major histopathological alterations observed in both mice and rats including sequestration of pRBCs, accumulation of hemozoin pigment and macrophage engulfing elements in microvasculature, disorganization of spleen architecture, and hyalinized membrane in alveolar wall.Systemic concentration of pro-inflammatory cytokines (TNF-α, IFNγ and IL-1α) and anti-inflammatory cytokines (IL-10, IL-4 and IL-13) were also quantified in mice and rats by using commercial ELISA kit. A distinctive difference obtained from analyzed data showed significant elevation of plasma TNF-α in malarial mice which contradict with low production of TNF-α along with significant concentrations of IL-10, IL-4 and IL-13 in serum of malarial rats. Thispattern of cytokine release has tipped towards the regulation of inflammatory response and survival during malaria infection. The protective role of the above said anti-inflammatory cytokines is not well elucidated, nor is there a relevance of these cytokines with the disease pattern or extent of vital organ dysfunction during the infection. Hence, the effects of systemic augmentation of IL-10, IL-4 and IL-13 on pathological conditions of malaria were investigated. P. berghei ANKA (PbA)-infected mice were treated with either the recombinant mouse (rm) IL-10, rmIL-4 or rmIL-13 and treatment with these cytokines has successfully delayed the mortality rate in all malarial mice with development of parasitaemia was reduced to as much as 20% during peak parasitaemia in relative to malaria mice receiving PBS. Body weight and rectal temperature also showed lesser extent of reduction. Results revealed the amelioration of malaria histopathological conditions in all examined organs upon treatment. Sequestration of pRBCs was reduced in the brain tissue. Hypertrophied Kupffer cells and sinusoids dilatation that were significant during malaria infection was lessen by treatment. The red and white pulp elements and central germinal structure were regained in spleen. Glomerular and tubular appearance of the treated malarial kidney appeared to be normal whilst the lung tissue of treated malarial mice were revealed to be normal without formation of hyalinized membrane and pigment deposition in alveolar septa. Taken together, it can be concluded that IL-10, IL-4 and IL-13 play significant role(s) during malaria infection and they may well serve as potential immunotherapeutic target strategy in malaria therapy.